A new ring-shape high-temperature superconducting trapped-field magnet. (4th August 2017) - Sheng, Jie; Zhang, Min; Wang, Yawei; Li, Xiaojian; Patel, Jay; Yuan, Weijia
Abstract: This paper presents a new trapped-field magnet made of second-generation high-temperature superconducting (2G HTS) rings. This so-called ring-shape 2G HTS magnet has the potential to provide much stronger magnetic fields relative to existing permanent magnets. Compared to existing 2G HTS trapped- field magnets, e.g. 2G HTS bulks and stacks, this new ring-shape 2G HTS magnet is more flexible in size and can be made into magnets with large dimensions for industrial applications. Effective magnetization is the key to being able to use trapped-field magnets. Therefore, this paper focuses on the magnetization mechanism of this new magnet using both experimental and numerical methods. Unique features have been identified and quantified for this new type of HTS magnet in the field cooling and zero field cooling process. The magnetization mechanism can be understood by the interaction between shielding currents and the penetration of external magnetic fields. An accumulation in the trapped field was observed by using multiple pulse field cooling. Three types of demagnetization were studied to measure the trapped-field decay for practical applications. Our results show that this new ring-shape HTS magnet is very promising in the trapping of a high magnetic field. As a super-permanent magnet, it will have a significant impact on large-scale industrial applications, e.g. the development of HTS machines with a very high power density and HTS magnetic resonance imaging devices.